The Role of Bali's Traditional Subak Farming System in the Preservation of Natural and Cultural Resources - Putu Doddy Heka Ardana; Dewa Oka Suparwata; Arief Sudrajat; Sri Chatun; Iwan Harsono (Westscience Press, 2024)
The Subak traditional farming system in Bali embodies a harmonious relationship between humans, nature, and spirituality, epitomizing the Balinese philosophy of